Evaluating the influence of operational parameters of pulsed light on wine related yeasts: focus on inter- and intra-specific variability sensitivity. (February 2023) - Harrouard, Jules; Pilard, Etienne; Miot-Sertier, Cécile; Pouget, Lena; Marullo, Philippe; Ferrari, Giovanna; Pataro, Gianpiero; Ghidossi, Rémy; Albertin, Warren
Abstract: In oenology, there is a growing demand by consumers for wines produced with less inputs (such as sulphite, frequently used for microbial control). Emerging control methods for managing microorganisms in wine are widely studied. In this study, the efficiency of pulsed light (PL) treatment was investigated. A drop-platted system was used to evaluate the impact of three PL operational parameters: the fluence per flash, the total fluence and the flash frequency. Fluence per flash appeared to be a key parameter prior to total fluence, thus demonstrating the importance of the effect of peak voltage during PL treatments. The efficiency of PL treatment was assessed on 198 strains distributed amongst fourteen yeast species related to wine environment, and an important variability in PL response was observed. Brettanomyces bruxellensis strains were strongly sensitive to PL, with intraspecific variation. PL was then applied to red wines inoculated with 9 strains of B. bruxellensis, Saccharomyces cerevisiae and Lachancea thermotolerans . Results confirmed interspecific response variability and a higher sensitivity of B. bruxellensis species to PL. Wine treatments with a total fluence of 22.8 J cm −2 resulted in more than 6 log reduction for different B. bruxellensis strains. These results highlight the potential of PL for wine microbial stabilization. Highlights: Pulsed light treatment was applied to 14 wine yeast species (198 strains). PL efficiency was driven by two main factors: fluence per flash and total fluence. The sensitivity to PL treatment varied depending on the species and the strains. Brettanomyces bruxellensis and other wine spoilers were highly sensitive to PL. Pulsed light treatment is promising for wine microbial stabilization.